Implementation of FE and Vitamin C Tablet Consumption on the Increase in Hemoglobin Levels in Pregnant Women at Ikua Koto Public Health Center - Epi Satria; Dian Eka Nursyam; Hasanalita Hasanalita; Febrina Febrina; Novi Maya Sari (PT. Riset Press International, 2026)
The risk of anemia in pregnant women is more severe if the hemoglobin level is less than 11 g/dL. Iron deficiency anemia is anemia that often occurs in pregnant women, generally due to deficiencies of key micronutrients in the hematopoiesis process, such as vitamin B12, folic acid, and iron. The purpose of this study was to examine the implementation of the consumption of Fe tablets and vitamin C on increasing hemoglobin levels in pregnant women at the Ikua Koto Community Health Center. The research design was a quasi-experiment, one group pre-test post-test design. With a sample of 30 respondents, with 2x observations, namely before and after the intervention. Statistical tests applied paired t-test tests. The analysis resulted in that the average hemoglobin level before the pre-test was 10.11 ± 0.49 g/dL, an increase of 11.04 ± 0.50 g/dL after treatment (post-test). The significance value obtained was p-value = 0.000 (p < 0.05), proving a significant difference in the variable hemoglobin levels before and after the intervention. It was concluded that consuming Fe tablets accompanied by vitamin C is very effective in increasing hemoglobin levels in pregnant women.